Faktor Pendukung dan Penghambat Niat Penggunaan Blockchain oleh Auditor di Kantor Akuntan Publik - Gero, Vinsensa M. S.; Sadha Suardikha, I Made (E-Jurnal Akuntansi, 2020)
This study aims to examine the factors that influence the intention to use Blockchain by auditors working at audit firm in Bali. The approach taken is based on a combination of the UTAUT and SQBT models. Performance Expectancy, Effort Expectancy, Socio-Cultural Factors and Facilitating Conditions are determined as enabler factors that support the intention to use Blockchain. The inhibiting factors were adapted from SQBT, namely Uncertainty, Loss Aversion, Sunk Costs and Regret Avoidance. The sampling method uses purposive sampling technique. The research data were obtained through a survey method and analysed using multiple linear regression. The results showed that effort expectancy and socio-cultural factors have positive influence on the intention to use Blockchain by auditors working at audit firm in Bali. Meanwhile, only sunk costs were found to have negative influence on the intention of using Blockchain by auditors. Keywords: Blockchain; Enabler; Inhibitor; Auditor.